2016
DOI: 10.1016/j.gloenvcha.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Spatially explicit assessment of water embodied in European trade: A product-level multi-regional input-output analysis

Abstract: Responsible water management in an era of globalised supply chains needs to consider both local and regional water balances and international trade. In this paper, we assess the water footprints of total final demand in the EU-27 at a very detailed product level and spatial scale-an important step towards informed water policy. We apply the multi-regional input-output (MRIO) model EXIOBASE, including water data, to track the distribution of water use along product supply chains within and across countries. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 38 publications
1
68
0
Order By: Relevance
“…These results were confirmed by Lutter et al [53]. They assessed the water footprints of total final demand in the EU-27 on a detailed product level and spatial scale, and found that the EU-27 import large volumes of green and blue virtual water, far exceeding the water used for domestic purposes.…”
Section: Name Description Referencessupporting
confidence: 57%
“…These results were confirmed by Lutter et al [53]. They assessed the water footprints of total final demand in the EU-27 on a detailed product level and spatial scale, and found that the EU-27 import large volumes of green and blue virtual water, far exceeding the water used for domestic purposes.…”
Section: Name Description Referencessupporting
confidence: 57%
“…This indicator is used to account for anthropogenic water appropriation (Lutter et al. ), but does not account for its contribution to water stress (Yang et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…The product resolution, however, is often low as highlighted in Feng et al (2012) and for example all agricultural goods are usually considered as a bulk or classified in few categories. Recent efforts in the MRIO analyses of water footprint are oriented to improving the product resolution (Lutter et al 2016).…”
Section: Box 2 the Water Footprint Calculationmentioning
confidence: 99%